Graduate school supervisees' relationships with their academic mentors. (14th September 2015) - Malik, Shahab Alam; Malik, Shujah Alam
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to observe different aspects of working relationships between supervisees/mentees with their academic supervisors/mentors from the mentees' perspective. Respondents were asked about networking, instrumental, psychological help received from their mentors and their working relationships with their mentors. Design/methodology/approach – A descriptive study was carried out in the COMSATS Institute of Information Technology, a public university of Pakistan. Data were collected from its main campus of Islamabad only, the capital of Pakistan. Respondents were Master of Science (MS) and PhD level students actively engaged in research projects/theses with their mentors. A final sample of 104 respondents was used for data analysis, comprising of 65 MS and 39 PhD students, from six departments offering graduate programs. Descriptive analysis was mainly used here to observe mean differences (ANOVA) based on control variables of supervisees gender, academic program, supervisor designation, gender and selection. Findings – Major significant mean scores differences were observed between supervisees who selected supervisors themselves and those who were assigned supervisors by the concerned department. In academic programs (MS vs PhD), some significant differences in instrumental and psychological help were observed, whereas no significant differences were found on gender basis (both supervisees and supervisors), supervisor designation and supervisees' category (full-time, part-time and faculty on leave). Originality/value – This study endeavored to observe relationships between supervisees and their supervisors in an academic environment using descriptive analysis. No such particular research in literature has been made earlier on national level and thus this study tries to fill that gap. This research's outcomes can be useful to all the concerned parties i.e. the mentor, supervisees and the graduate school. Mentors can assess how supervisees rate the supervision style and contribution. Supervisees can benefit from the experiences of their fellows and the graduate schools can assess which aspects of relationship matter most to the supervisees at different levels.